2018
DOI: 10.1111/corg.12226
|View full text |Cite
|
Sign up to set email alerts
|

Founding family and auditor choice: Evidence from Taiwan

Abstract: Manuscript Type Empirical Research Question/Issue From an agency perspective, we investigate whether family ownership and control configurations are systematically associated with a firm's choice of auditor. Our analysis focuses on three different characteristics of family ownership and control: family ownership (cash flow rights), disparity between cash flow and voting rights held by family owners (cash–vote divergence), and the family identities of CEOs. Research Findings/Insights Our findings suggest that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 105 publications
0
43
0
Order By: Relevance
“…As a result, a family-controlled firm may provide a competitive advantage and improve firm performance (Anderson and Reeb, 2003). A number of other empirical studies also show that family ownership is correlated with better performance (Bonilla et al, 2010;Carney and Gedajlovic, 2002;Hsu et al, 2018;Joh, 2003;Maury, 2006;Villalonga and Amit, 2006;Wang and Shailer, 2017). When all the evidence is taken together, since the impact of family ownership on firm performance is an empirical issue, the following hypothesis is then proposed:…”
Section: Ownership Structure and Firm Performancementioning
confidence: 99%
“…As a result, a family-controlled firm may provide a competitive advantage and improve firm performance (Anderson and Reeb, 2003). A number of other empirical studies also show that family ownership is correlated with better performance (Bonilla et al, 2010;Carney and Gedajlovic, 2002;Hsu et al, 2018;Joh, 2003;Maury, 2006;Villalonga and Amit, 2006;Wang and Shailer, 2017). When all the evidence is taken together, since the impact of family ownership on firm performance is an empirical issue, the following hypothesis is then proposed:…”
Section: Ownership Structure and Firm Performancementioning
confidence: 99%
“…Chen, Cheng, and Dai () argued that the selection of an auditor depends on the person or individuals who run the business, because the founder, descendants, and professional CEOs vary with respect to their sense of identity, psychological attachment to the firm, and management incentive mechanisms. Following this, Hsu et al () categorized family firms as those run by a founder CEO, descendant CEO, or professional CEO to examine their variability in selecting an auditor. Consistently, Hsu et al () evidenced that family firms do not tend to appoint high‐quality auditors when family alignment is present (i.e., high family ownership and the presence of a founding CEO), due to less outside investor demand for such auditors.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
“…Following this, Hsu et al () categorized family firms as those run by a founder CEO, descendant CEO, or professional CEO to examine their variability in selecting an auditor. Consistently, Hsu et al () evidenced that family firms do not tend to appoint high‐quality auditors when family alignment is present (i.e., high family ownership and the presence of a founding CEO), due to less outside investor demand for such auditors. AL‐Qadasi, Abidin, and Al‐Jaifi () suggested that Malaysian family firms, although they rely more upon external as opposed to internal auditors, are unlikely to appoint industry‐specialist auditors.…”
Section: Determinants Of Auditor Choicementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous related studies (e.g., Hope et al 2008;Ben-Hassoun et al 2018) suggest that company's leverage may influence auditor choice as it is considered a proxy for audit risks (e.g., Chan et al 1993;Whisenant et al 2003). Accordingly, and consistent with similar previous research (e.g., Hsu et al 2018;Ben-Hassoun et al 2018;Hsu et al 2015;Lin and Liu, 2009), the LEV variable is added to the regression model as a measure of company's leverage. This variable is measured as the company's long-term liabilities to total assets, and is expected to have a positive regression coefficient.…”
Section: Control Variablesmentioning
confidence: 64%